Intestinal Microbial Products From Alcohol‐Fed Mice Contribute to Intestinal Permeability and Peripheral Immune Activation. (5th September 2019) - Samuelson, Derrick R.; Gu, Min; Shellito, Judd E.; Molina, Patricia E.; Taylor, Christopher M.; Luo, Meng; Welsh, David A.
Abstract : Background: Alcohol use causes significant disruption of intestinal microbial communities, yet exactly how these dysbiotic communities interact with the host is unclear. We sought to understand the role of microbial products associated with alcohol dysbiosis in mice on intestinal permeability and immune activation in an in vitro model system. Methods: Microbiota samples from binge‐on‐chronic alcohol‐fed and pair‐fed male and female mice were cultured in Gifu Anaerobic Broth for 24 hours under anaerobic conditions. Live/whole organisms were removed, and microbial products were collected and added to human peripheral blood mononuclear cells (PBMCs) or polarized C2BBe1 intestinal epithelial monolayers. Following stimulation, transepithelial electrical resistance (TEER) was measured using a volt/ohm meter and immune activation of PBMC was assessed via flow cytometry. Results: Microbial products from male and female alcohol‐fed mice significantly decreased TEER (mean percentage change from baseline alcohol‐fed 0.86 Ω/cm 2 vs. pair‐fed 1.10 Ω/cm 2 ) compared to microbial products from control mice. Following ex vivo stimulation, immune activation of PBMC was assessed via flow cytometry. We found that microbial products from alcohol‐fed mice significantly increased the percentage of CD38+ CD4+ (mean alcohol‐fed 17.32% ± 0.683% standard deviation (SD) vs. mean pair‐fed 14.2% ± 1.21% SD, p  < 0.05) and CD8+ (mean alcohol‐fed 20.28% ± 0.88% SD vs. mean pair‐fed 12.58% ± 3.59% SD, p  < 0.05) T cells. Conclusions: Collectively, these data suggest that microbial products contribute to immune activation and intestinal permeability associated with alcohol dysbiosis. Further, utilization of these ex vivo microbial product assays will allow us to rapidly assess the impact of microbial products on intestinal permeability and immune activation and to identify probiotic therapies to ameliorate these defects. Abstract : Chronic alcohol use leads to immune dysfunction, such as impaired host defense and increased inflammation. We found that treatment with alcohol‐associated intestinal microbial products lead to a decrease in epithelial barrier function, as well as increased activation of peripheral T‐cells. Taken together, these data suggest that changes in the microbial products produced by the gut microbiota contribute, in part, to the immune dysfunction that is seen following chronic alcohol consumption.